EMMPRIN promotes spheroid organization and metastatic formation: comparison between monolayers and spheroids of CT26 colon carcinoma cells - Gabriele Feigelman; Gabriele Feigelman; Elina Simanovich; Phillipp Brockmeyer; Michal A. Rahat; Michal A. Rahat (Frontiers in Immunology, 2024)
BackgroundIn vitro studies often use two-dimensional (2D) monolayers, but 3D cell organization, such as in spheroids, better mimics the complexity of solid tumors. To metastasize, cancer cells undergo the process of epithelial-to-mesenchymal transition (EMT) to become more invasive and pro-angiogenic, with expression of both epithelial and mesenchymal markers.AimsWe asked whether EMMPRIN/CD147 contributes to the formation of the 3D spheroid structure, and whether spheroids, which are often used to study proliferation and drug resistance, could better model the EMT process and the metastatic properties of cells, and improve our understanding of the role of EMMPRIN in them.MethodsWe used the parental mouse CT26 colon carcinoma (CT26-WT) cells, and infected them with a lentivirus vector to knock down EMMPRIN expression (CT26-KD cells), or with an empty lentivirus vector (CT26-NC) that served as a negative control. In some cases, we repeated the experiments with the 4T1 or LLC cell lines. We compared the magnitude of change between CT26-KD and CT26-WT/NC cells in different metastatic properties in cells seeded as monolayers or as spheroids formed by the scaffold-free liquid overlay method.ResultsWe show that reduced EMMPRIN expression changed the morphology of cells and their spatial organization in both 2D and 3D models. The 3D models more clearly demonstrated how reduced EMMPRIN expression inhibited proliferation and the angiogenic potential, while it enhanced drug resistance, invasiveness, and EMT status, and moreover it enhanced cell dormancy and prevented CT26-KD cells from forming metastatic-like lesions when seeded on basement membrane extract (BME). Most interestingly, this approach enabled us to identify that EMMPRIN and miR-146a-5p form a negative feedback loop, thus identifying a key mechanism for EMMPRIN activities. These results underline EMMPRIN role as a gatekeeper that prevents dormancy, and suggest that EMMPRIN links EMT characteristics to the process of spheroid formation.ConclusionsThus, 3D models can help identify mechanisms by which EMMPRIN facilitates tumor and metastasis progression, which might render EMMPRIN as a promising target for anti-metastatic tumor therapy.